A water-soluble thiophene-croconaine dye with a high molar extinction coefficient for NIR fluorescence imaging-guided synergistic photothermal/photodynamic therapy of cancer. Issue 47 (21st November 2022) - Pang, E; Huang, Rong; Zhao, Shaojing; Yang, Ke; Li, Baoling; Tan, Qiuxia; Tan, Siyi; Lan, Minhuan; Wang, Benhua; Song, Xiangzhi
Abstract : A water-soluble thiophene-croconaine dye with a high molar extinction coefficient for NIR fluorescence imaging-guided synergistic photothermal/photodynamic therapy of cancer. Abstract : Phototherapeutic agents with near-infrared (NIR) fluorescence, strong reactive oxygen species generation and photothermal conversion capabilities are highly desirable for use in cancer therapy. Herein, a water-soluble NIR croconaine dye (TCR ) with a thiophene-croconaine rigid core and two symmetric alkyl chains was designed and synthesized. TCR exhibits intense NIR absorption and fluorescence that peaked at 780 and 815 nm, respectively, with a high molar extinction coefficient of 1.19 × 10 5 M −1 cm −1 . Moreover, TCR has a high photothermal conversion efficiency of 77% and is capable of generating hydroxyl radicals (OH˙) under 735 nm laser irradiation. Based on these outstanding properties, TCR has proven its application in NIR fluorescence imaging-guided synergistic photothermal/photodynamic therapy of cancer.